“WO”man of the People: - Rumana Siddique (Crossings, 2017)
Gendered assumptions of nationalism have been an integral part of liberation and post-liberation theory and fiction resulting in the construction of disempowered national identities for women in the modern African states. The narratives of idealization and mythologizing sketch women in the developing literary canvas as symbolic or biological figures who had no active social or political roles or voices. This paper focuses on how gender roles in national identity and nation-building have evolved in the works of the major male African writer Chinua Achebe. It examines the narratives that have reinforced or challenged Achebe with particular focus on how the portrayal of women in his final novel stands him as a progressive in terms of a new vision of the role and space of women in modern Africa.